Potential reaction initiation points of polycyclic aromatic hydrocarbons - Reizer Edina; Fiser Béla; Bela Fiser; Фішер Бейло (Elsevier, 2022)
Abstract. Reaction initiation points of the 16 priority polycyclic aromatic hydrocarbons (PAHs) have been determined by calculating all the different C-H bond dissociation enthalpy (BDE) values. Six density functional theory methods (B3LYP, B3LYP-D3, B97D3, M06-LD3, M06-2X-D3, and ωB97X-D) in combination with 4 basis sets (6-31G(d), 6-31+G(d,p), 6-311++G(d,p), def2-TZVP) have been applied and the most feasible combination has been selected. The BDE values and the corresponding bond lengths have been used to determine potential attack points on the structures. The studied molecules have been categorized structurally as well, within which the position of the hydrogen atoms is considered. Results show that most of the hydrogens are in zig-zag positions, and the BDE and bond length values for the 16 priority PAHs are in a range between 342.0 and 485.6 kJ/mol and 1.0817–1.952 Å, respectively. Most of the initiation points are represented by armchair and peak hydrogens. The lowest and highest BDE and shortest and longest bond length values belong to fluorene and acenaphthylene where the hydrogens were aliphatic and in peak position, respectively.
Editorial Board: https://arabjchem.org/editorial-board/
Contents: https://arabjchem.org/issue/2022-15-6/
Keywords: PAH; Bond dissociation enthalpy; BDE; DFT; C-H bond